Anodic Polarization of Mild Steel in Saturated C a(OH)2 Contaminated with NaCl in Presence of NaNO2 - S. Yaro, Aprael; S. Hassan, Hany (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The corrosion behavior of mild sleet in saturated aerated and de-aerated Ca(OH)2 solution was investigated using electrochemical measurements. The work was carried out with small coupons immersed in solutions containing different quantities of NaCl in presence of various NaN02 concentrations as corrosion inhibitors. It has been found thal:(1 ) In presence of NaCl, the time required to reach O2 evolution potential in de-aerated Ca(OH)2 polarized at 10μA/cm 2 is function of inhibitor concentration and it becomes lass as NaN02 increases compared with zero presence indicating the effectiveness of NaN02 as anodic corrosion inhibitor. (2) In absence of NaCl, the Lime required to reach O2 evolution potential in de-aerated solutions is less that in aerated solutions when inhibitor increases from 0 to 0.3 wt. %. (3) In presence of sufficient chloride in de-aerated Ca(OH)i solution, the passive film may broken down locally.